Growth inhibition and morphological alterations of Staphylococcus aureus caused by the essential oil of Aloysia triphylla - Oliva, Maria de Las Mercedes (2015)
Aloysia triphylla essential oil (EO) has antimicrobial activity on Staphylococcus aureus which is a pathogen responsible for severe infections and food contamination. The target of EO is mainly in the cytoplasmic membrane. In this work the mechanisms of action of the EO of A. triphylla on S. aureus were investigated. A. triphylla was collected from La Paz. The oil was analyzed by GC-MS. The antimicrobial effects were evaluated by MIC, MBC, killing time and TEM. MIC values were 23 µg/mL for 6.3 x 104 CFU/mL, 92 µg/mL for 5.71 x 105 CFU/mL and 180 µg/mL for 9 x 106 CFU/mL. The MBC was 5920 µg/mL for all cellular concentrations and it was necessary more time to kill bigger cell populations. Multilamellar and mesosome-like structures on the membrane were seen by TEM. A. triphylla oil is an antibacterial compound against S. aureus which main mechanism of action seems to be the cytoplasmic membrane disruption.